2020
DOI: 10.3389/fevo.2019.00509
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Life of Echinoderm Larvae

Abstract: Echinoderm larvae have served as a fundamental system for understanding development and life history evolution over much of the last century. In the last few decades, our understanding of echinoderm larvae has expanded to the microbiota that they associate with. These symbionts and the communities that they form in relation to echinoderm larval host are the focus of this review. Our synthesis of the literature suggests three primary themes. First, larval echinoderms associate with "subcuticle bacteria" that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…We qualitatively and quantitatively compared the microbiome of both Heliocidaris sister species to test whether lecithotrophic developers associate with a bacterial community that is less diverse and less abundant than planktotrophic developers. Consistent with other echinoderm larvae (16,23), the bacterial communities of H. tuberculata and H. erythrogramma are species-specific and are distinct from the seawater microbiome throughout development (permutational multivariate analysis of variance [PERMANOVA], unweighted and weighted UniFrac, P < 0.001; SI Appendix, Fig. S1 and Table S1).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…We qualitatively and quantitatively compared the microbiome of both Heliocidaris sister species to test whether lecithotrophic developers associate with a bacterial community that is less diverse and less abundant than planktotrophic developers. Consistent with other echinoderm larvae (16,23), the bacterial communities of H. tuberculata and H. erythrogramma are species-specific and are distinct from the seawater microbiome throughout development (permutational multivariate analysis of variance [PERMANOVA], unweighted and weighted UniFrac, P < 0.001; SI Appendix, Fig. S1 and Table S1).…”
Section: Resultssupporting
confidence: 63%
“…The planktotrophic larvae of several echinoderm species associate with bacterial communities that are taxonomically and compositionally specific to food availability (16,23). When diet restriction is prolonged and morphological plasticity is expressed, planktotrophic larvae exhibit shifts in their bacterial community that precede and then correlate with the expression of morphological plasticity (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic bacteria widely identified in the gut microflora from varied marine invertebrates ( Carrier and Reitzel, 2020 ) Ca. Hepatoplasma, as a symbiotic bacterium, are comparatively stable intestinal members, which are reported in a variety of the isopod species ( Sebastian and Zimmer, 2008 ; Cheng et al, 2019 ), sea urchin ( Li et al, 2018 ), and shrimps ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects could depend on the bacterial doses used in our assay, which are presumably much higher than those encountered in the ocean by free-living echinoderm embryos. In support of this hypothesis, previous reports showed that many bacterial strains normally associate with healthy sea urchin larvae, where they behave as commensal or mutualistic microorganisms (reviewed in 69 ). However, under dysbiosis conditions an excessive bacterial load can overwhelm larval defenses, thereby affecting larval welfare and physiology 66 , 70 .…”
Section: Discussionmentioning
confidence: 69%